Study of the Legalization of Children Outside of Marriage in the Perspective of the Marriage Law Number 16 of 2019 and Legislation - Veni Apreliasari; Dwi Putra Jaya; Sandi Aprianto (JURNAL HUKUM SEHASEN, 2023)
The objectives of this research are: 1. To find out the legalization of children outside of marriage in the perspective of the Marriage Law Number 16 of 2019 and laws and regulations? 2.To find out and explain the Legalization of a Child Out of Marriage in the Perspective of the Marriage Law Number 16 of 2019 and Legislation? This type of research is normative through library research by tracing various rules related to research, reviewed From various literature, journals, books and judges' decisions which are important study guidelines in this study, this research technique is in the form of collecting data or analyzing research that has been used by previous researchers. Research results 1. Legalization of children outside of marriage in the perspective of the Marriage Law No. 16 of 2019 and statutory regulations. An endorsement must be preceded by an acknowledgment. Likewise with the letter of ratification of a child out of wedlock, it must be preceded by an acknowledgment from both parents. A letter of authorization for a child out of wedlock is a legal tool (rechts middle) to give the child the position (status) as a legitimate child. As a result of the recognition of a child out of wedlock, namely the emergence of a civil relationship between the child and the father or mother who recognizes it. With the emergence of this Civil relationship, the status of children out of wedlock changes to those of children out of wedlock who have been recognized, their position is far better than children out of wedlock who are not recognized. 2. Implementation of Legalization of Children Outside of Marriage in the Perspective of the Marriage Law Number 16 of 2019 and Legislation it applies the provisions of the same law, as if the child was born in a marriage, which means that the child has the same position as children born throughout the marriage. These children obtain the status of legal children, not only to their parents but to the parents' relatives.